2020
DOI: 10.3324/haematol.2020.267294
|View full text |Cite
|
Sign up to set email alerts
|

Phenogenomic heterogeneity of post-transplant plasmablastic lymphomas

Abstract: Plasmablastic lymphoma (PBL) is a rare and clinically aggressive neoplasm that typically occurs in immunocompromised individuals, including those with HIV infection and solid organ allograft recipients. Most prior studies have focused on delineating the clinicopathologic features and genetic attributes of HIV-related PBLs, where MYC deregulation and EBV infection, and more recently, mutations in JAK/STAT, MAP kinase, and NOTCH pathway genes have been implicated in disease pathogenesis. The phenotypic spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…33 PBL is an aggressive B-cell lymphoma usually arising in an immunosuppressive setting, such as HIV infection, but also occurs in an immunocompetent setting. [34][35][36] It usually affects adult males who present with extranodal disease and advanced stage of disease. 35,37 The histopathological presentation is characterized by a diffuse infiltrate of large, atypical cells with round to oval central or peripheral nuclei, single nucleoli, and abundant amphophilic cytoplasm, resembling an immunoblast or a plasmablast.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…33 PBL is an aggressive B-cell lymphoma usually arising in an immunosuppressive setting, such as HIV infection, but also occurs in an immunocompetent setting. [34][35][36] It usually affects adult males who present with extranodal disease and advanced stage of disease. 35,37 The histopathological presentation is characterized by a diffuse infiltrate of large, atypical cells with round to oval central or peripheral nuclei, single nucleoli, and abundant amphophilic cytoplasm, resembling an immunoblast or a plasmablast.…”
Section: Diagnosismentioning
confidence: 99%
“…PBL is an aggressive B‐cell lymphoma usually arising in an immunosuppressive setting, such as HIV infection, but also occurs in an immunocompetent setting 34–36 . It usually affects adult males who present with extranodal disease and advanced stage of disease 35,37 .…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In regard to the association with prognosis, Frontzek et al reported a trend toward unfavorable outcomes in PBL patients with NRAS aberrations [52]. Recurrent RAS/RAF aberrations (55% of mutation incidence) were also identified in post-transplant PBLs, a rare type of post-transplant lymphoproliferative disorder accounting for 5-14% of PBL cases [133]. The ctivation of RAS-MAPK signaling emerges as a pathogenetic mechanism in plasma cell dyscrasias, [49] and the therapeutic potential of RAS/RAF/MEK/ERK inhibition should be addressed in PBL [52].…”
Section: Other Plasma Cell Related Diseasesmentioning
confidence: 99%
“…Recurrent mutations in epigenetic modifiers, such as the KMT2/MLL family of histone H3 methyltransferases were among the most frequent alterations. Treatment was variable, mainly including rituximab and/or chemotherapy (sometimes with addition of bortezomib) with or without radiation; however, given the heterogeneity, no conclusions can be made [ 142 ]. Another case series of eight patients combined IST reduction with systemic chemotherapy; however, five patients died from early progression.…”
Section: Treatmentmentioning
confidence: 99%